A Comparison Between the Institutionalized Elderlies Versus Those in Community-Dwelling in Iran - Ataollah Masnavi; Ahmad Ali Akbari Kamrani; Seyed Ahmad Hoseini (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: Ageing of population is a new phenomenon that has occurred in recent center especially in developed countries and it has named as "papy Bomb” In developing countries also there are some problems due to Family pattern changes and transition to Nuclear Family. Methods & Materials: In Iran, elderly population is increased during two decade and elder lies plus 60 years from 5.43% in 1986 are increased to 7.27% in 2006. Results: The total population of Iran was more than 70 millions in 2006 and there was more than 5 million elder lies plus 60 years. Conclusion: The Augmentation of elderly population in Iran is one of our motivation for investigation and assessment of status between the elder lies lives in institutes and whose lives in Community - dwelling.